MIGRATION AND THE MAGGARAIANSâ€™ CULTURAL IDENTITY AS REPRESENTED IN MAGGARAIAN RAP SONGS - Yuliantari, Ans Prawati (Sanata Dharma University, 2020)
One significant factor that has brought the Manggaraians into contact with many people from various cultures outside their place of origin is migration. Their awareness of the importance of preserving and retaining their cultural identity is growing once they experience intercultural interactions. Rap songs have become one of the means by which they observe migration and cultural identity closer as important phenomena in their life.Â Â Â Â Â Â Â Â Â Â Â The present article studies these phenomena in Manggaraian rap songs. For this purpose, the concept of â€œrural idyllâ€ suggested by Marc Mormont is used to understand the Manggaraiansâ€™ perspective on their home region, and the concept of identity as defined by Stuart Hall is used to examine the way the Manggaraians construe their cultural identity. This study is focused on 30 Manggaraian rap song that feature migration and Manggaraian cultural identity as the themes of the lyrics.Â Â Â Â Â Â Â Â Â Â Â The study has led to the insight that the main reasons that motivate the Manggaraians to migrate are their desires to continue their education, find better livelihood, gain new experiences in foreign regions and look for better accesses and facilities that are unavailable in their home region to achieve their goals. The experience of living among people from many different cultures in foreign regions confront them with the need to maintain their cultural identity and contact with their home region. To fulfill this need they make attempts of revitalizing Manggaraian traditional values that they are familiar with throughout their growing-up years in Manggarai.